2019
DOI: 10.3390/w11061139
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Version 5 (V05) of Integrated Multi-Satellite Retrievals for Global Precipitation Measurement (IMERG) over the Tianshan Mountains of China

Abstract: This study evaluated the performance of the Integrated Multi-satellite Retrievals for Global Precipitation Measurement (IMERG) version 5 (V05) Early-run and Final-run (IMERG-E and IMERG-F, respectively) products over the Tianshan Mountains. For comparison, the accuracies of two Tropical Rainfall Measuring Mission (TRMM) products (3B42RT and 3B42V7) were also analyzed. Performance of the satellite-based precipitation products (SPPs) was analyzed at daily to annual scales from April 2014 to October 2017. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
3
9
0
Order By: Relevance
“…Gauge-based records showed a gradual decrease in the average daily precipitation amounts from the northwest to the southeast. Similar distributions of average daily precipitation in the Tianshan Mountains were found in a previous study [41]. Generally, all SPPs were able to capture the spatial distribution of precipitation, albeit SPPs showed considerable overestimation/underestimation of precipitation amounts at different stations.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…Gauge-based records showed a gradual decrease in the average daily precipitation amounts from the northwest to the southeast. Similar distributions of average daily precipitation in the Tianshan Mountains were found in a previous study [41]. Generally, all SPPs were able to capture the spatial distribution of precipitation, albeit SPPs showed considerable overestimation/underestimation of precipitation amounts at different stations.…”
Section: Methodssupporting
confidence: 84%
“…The Chinese National Meteorological Information Centre had ensured the high quality of daily time-series data of the selected gauging stations. Moreover, many recent hydrological and climatological studies have successfully utilized the precipitation data of the considered gauging stations [5,41,44,48]. Considering the availability and quality of the gauge-based observations, this study was designed for the period from June 2014 to December 2017.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…With their annual CC and RB values exceeding the good performance thresholds, both IMERG_F and 3B42 can be regarded as reliable sources of monthly precipitation in the SRB. Similar to our study, previous studies have also observed satisfactory performance of IMERG_F and 3B42 in monthly rainfall estimation [43,44]. Figure 3 compares the spatial distribution of the four annual continuous evaluation metrics among the SPPs at the monthly scale.…”
Section: Evaluation At the Monthly Scalesupporting
confidence: 88%
“…Recent advancements in satellite-mounted rainfall detection sensors and data retrieval algorithms have enabled researchers and other data users to utilize rainfall data at fine spatial and temporal scales. The satellite-based rainfall products (SRPs) can provide continuous information on rainfall's occurrence, intensity, and quantity [6,7]. Generally, these SRPs provide rainfall estimates based on data from passive microwave (MW) sensors, infrared (IR) sensors, or a combination of the two datasets.…”
Section: Introductionmentioning
confidence: 99%